Analisis Determinan Kejadian Hipertensi : Studi di Wilayah Urban Kabupaten Wonogiri - Latar, Zulfikar Sakti; Suhartono, Suhartono; Martini, Martini; Harriyani, Ika (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2025)
Background: Hypertension, known as the silent killer, has a morbidity rate of 40% in developing countries, with Indonesia reporting a prevalence of 34%. Urban areas show the highest rates. In 2018, the prevalence of hypertension in Wonogiri Regency was 45.9% (Riskesdas). In 2023, data from the Wonogiri Health Office recorded 69,663 urban and 48,223 rural hypertension cases. The objective of this study is to identify key determinants contributing to the prevalence of hypertension in urban communities within Wonogiri Regency.Methods: This was a non-experimental quantitative study with a case-control and survey design. A total 175 cases : 175 controls aged 15–65 years were selected using multistage random sampling. Analyze data using Chi-square and multiple logistic regression tests.Results: the study found Significant factors associated with hypertension included: family history of hypertension (OR 5,6; 95% CI: 3,2–9,6), age ≥ 45 years (OR 3,9; 95% CI: 2,2–6.8), low education level (OR 2,8; 95% CI: 1,6–4,8), frequent consumption of salty foods (OR 2,6; 95% CI: 1,5–4,4), obesity (OR 2,4; 95% CI: 1,4–4,3), and low physical activity (OR 1,9; 95% CI: 1,2–3,0). The R² value of 0.404 indicates that these variables contribute 40.4% to the incidence of hypertension in urban areas, while the remaining 59.6% is attributed to other factors not examined in this study.Conclusion: The risk of hypertension in the urban areas of Wonogiri Regency is significantly associated with having a family history of hypertension, being aged ≥ 45 years, low educational level, frequent consumption of salty foods, obesity, and low levels of physical activity.